The Late Albert Hourani and Orientalism - Piterberg, Gabriel (Jama’a: an Interdisciplinary Journal of Middle East Studies, 1997)
The article proposes a framework for the examination of Albert Hourani’s varied contribution to the study of the Middle East. The main argument is that in the late 1960s Hourani’s thinking and writing underwent a major shift: from Orientalism to history. It is further argued that this shift was dialectical, and that it was embodied in Hourani’s growing interest in Ottoman history and, in particular, in the Ottoman Middle East. The article consists of two parts: the first surveys Hourani’s explicit views on the work of Edward Said, the debate it has given rise to and Said’s references to Hourani’s views; the second part discusses Hourani’s own work in the light of the question of Orientalism.